Study on shelf life of non-preservative containing mango drinks produced in Dhaka, Bangladesh - Hasan, Md Mehadee; Kabir, Md Shahidul (Stamford Journal of Microbiology, 2015)
This study was carried out to determine shelf life of aseptically filled non-preservative containing mango drinks. Microbiological sterility was considered as the parameter for determining the shelf life of those samples as they were aseptically filled non-preservative containing sterile mango drinks. Samples were randomly collected from 30 different batches for shelf life assay. All samples (100%) were found to remain sterile up to 4 months. 70% of total samples showed no growth of microorganisms up to 5 months. 33.3% of total samples showed microbial growth after 6 months. Only 6.7% of total samples demonstrated no growth of microorganisms up to 7 months following manufacture. This study demonstrates that minimum shelf life of aseptically filled non-preservative containing mango drinks was 4 months and they may be considered safe if they are consumed within this period of time. If these drinks are taken after 4 months will bear the risk of foodborne infection and outbreak of diseases. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22757 Stamford Journal of Microbiology, Vol.4(1) 2014: 24-27